2013
DOI: 10.1007/s11274-013-1533-8
|View full text |Cite
|
Sign up to set email alerts
|

Environmental context shapes the bacterial community structure associated to Peltigera cyanolichens growing in Tierra del Fuego, Chile

Abstract: The structure of the associated bacterial community of bipartite cyanolichens of the genus Peltigera from three different environmental contexts in the Karukinka Natural Park, Tierra del Fuego, Chile, was assessed. The sampling sites represent different habitat contexts: mature native forest, young native forest and grassland. Recently it has been determined that the bacterial community associated to lichens could be highly structured according to the mycobiont or photobiont identities, to the environmental co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…For example, species from the P. neckeri lineage (related to M7) and P. hymenina lineage (related to M8) were rare in South America ( 25 , 40 ), being defined commonly as circumpolar ( 25 ). Furthermore, to the best of our knowledge, there have been no reports of P. ponojensis (related to M1) in South America, except for our previous studies from Karukinka ( 41 , 42 ). One specimen, M3, was not related to any published sequence from the database, indicating that it could corresponded to a new undescribed species.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…For example, species from the P. neckeri lineage (related to M7) and P. hymenina lineage (related to M8) were rare in South America ( 25 , 40 ), being defined commonly as circumpolar ( 25 ). Furthermore, to the best of our knowledge, there have been no reports of P. ponojensis (related to M1) in South America, except for our previous studies from Karukinka ( 41 , 42 ). One specimen, M3, was not related to any published sequence from the database, indicating that it could corresponded to a new undescribed species.…”
Section: Discussionmentioning
confidence: 69%
“…Quilhot et al ( 40 ) reported the lichen diversity in Aysén Region (~110,000 km 2 ), in which the Coyhaique National Reserve (21,500 km 2 ) is located, and detected 13 species from which one of our mycobionts was not reported (M1, related to P. ponojensis ). On the other hand, the only published studies on Peltigera at Karukinka corresponded to a previous baseline study conducted in different areas of the park ( 2 ) and our previous studies ( 41 , 42 ), which included the same Karukinka specimens analyzed in the present study. In the other two sites, previous studies only found a small number of species including P. rufescens in the case of Navarino ( 26 ) and P. didactyla in Deception Island ( 3 , 37 , 49 ).…”
Section: Discussionmentioning
confidence: 80%
“…In fact, the communities of the lichen thalli are different from those of the substrates where they grow. Although, they share certain bacteria in common [17,20]. Moreover, the lichen substrate has been proposed as one of the sources of cyanobionts [21], reinforcing the proposal that there could be a selection of members of the symbiosis from this underlying environment [17,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, when we statistically compared the consumption of each carbon-source by the microbiotas of these two lichen pairs (M5C01 and M6C01), we verified that 12 out of the 31 carbon-sources were consumed equally ( d -Cellobiose, i-erythritol, d -mannitol, γ-hydroxybutyric acid, α-ketobutyric acid, d -malic acid, 2-hydroxybenzoic acid, l -phenylalanine, l -serine, l -threonine, Tween 80, and α-cyclodextrin) ( Table 1 ). Few studies distinguish microbial communities associated with the thallus versus those associated with the substrates where lichens grow [ 41 , 42 , 70 ], but they all agree that bacteria associated with the lichen thalli could be recruited, at least in part, from the substrates where lichens grow.…”
Section: Resultsmentioning
confidence: 99%
“…Several factors have been identified as descriptors of the lichen bacterial microbiome structure, including both intrinsic and extrinsic factors [ 28 , 39 , 40 , 41 ]. In a previous study, we discovered that the metabolic structure of the bacterial microbiota in Peltigera thallus was influenced by mycobiont identity and by the production of phenoloxidase activity, while the metabolic structure of the bacterial microbiota present in the substrates where lichens grow was shaped by cyanobiont identity and the sampling site [ 42 ].…”
Section: Introductionmentioning
confidence: 99%